Job Stress among Academic Staff : A Cross-cultural Qualitative Study - Triantoro Safaria (Intelektual Pustaka Media Utama, 2013)
The aim of this study is to explore the sources of job stress and type of coping among academic staff from two countries; namely Pahang, Malaysia and Yogyakarta, Indonesia. This study used qualitative design, and phenomenology technique conducted to analyze the data. Twenty two academic staffs were involved in this study. The result found several interesting findings. Seven stressors categories were found; (1) inadequate role occupancy, (2) increasing work demands, (3) deficient role preparedness, (4) insufficient role support, (5) role ambiguity, (6) role conflict and (7) work-family conflict. There were four responses of stress that was showed by university academic staffs, namely: (1) behavioral responses, (2) emotional responses, (3) cognitive responses, and (4) physiological responses. The reason that lead respondents still continue work as academic staff are (1) being a lecturer was the choice of his/her life, (2) teaching was noble work, (3) could share knowledge with others/students, (4) love the profession as a lecturer, and (5) feel happy to teach and discuss with students. The coping strategy that always used by academic staffs to cope with job related stress were five coping strategy patterns, namely: (1) problem focused coping, (2) emotion focused coping, (3) seeking social support, (4) using religious coping, and (5) making meaning.DOI: http://dx.doi.org/10.11591/ijphs.v2i2.2427